Deep eutectic solvents as performance additives in biphasic reactions. Issue 64 (18th August 2017) - Lan, Dongming; Wang, Xuping; Zhou, Pengfei; Hollmann, Frank; Wang, Yonghua
Abstract : Deep eutectic solvents act as surfactants in biphasic (hydrophobic/aqueous) reaction mixtures enabling higher interfacial surface areas at lower mechanical stress as compared to simple emulsions. Abstract : Deep eutectic solvents act as surfactants in biphasic (hydrophobic/aqueous) reaction mixtures enabling higher interfacial surface areas at lower mechanical stress as compared to simple emulsions. Exploiting this effect the rate of a chemoenzymatic epoxidation reaction was increased more than six-fold.